Complete mitochondrial genome and phylogenetic analysis of Danio roseus (Teleostei, Cypriniformes, Danionidae). Issue 2 (1st February 2022) - Song, Lin; Chen, Xiao Jiang; Han, Xing Peng; Gu, Yi Wen
Abstract: Danio roseus, collected from Gadu River in Yingjiang area, Yunnan Province, China, had been sequenced on Illumina HiSeq platform with 16523 bp in length, which included 37 genes encoding 13 proteins-coding genes (PCGs), 22 tRNAs, 2 rRNAs and a displacement loop region. The proportion of nucleotides in mitochondrial genome was T (28.7%), C (23.2%), A (32.3%), G (15.8%) with an AT bias of 61%. Maximum-Likelihood phylogenetic tree was reconstructed using concatenated mitochondrial protein-coding genes of D. roseus and other 12 fishes. The result of phylogenetic analysis supported the consanguineous relationship among D. roseus, D. rerio, D. nigrofasciatus and D. dangila .